S-scheme heterojunction photocatalyst P25/CuI - Nadareishvili, M.; edginidze, T. Z; Kurtanidze, A.; Mdzinarashvili, M.; Ramsden, J. (Edelweiss Applied Science and Technology, 2025)
The S-Scheme photocatalyst P25/CuI was developed based on the commercial photocatalyst P25. Comparative studies were conducted to examine the properties of this photocatalyst, as well as cluster-free P25 and P25/Co, which is decorated with metal clusters. The structural features of these materials were analyzed using X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDS). It was found that the starting material P25 consisted of a mixture of two modifications of titanium dioxide (TiO2): anatase and rutile, with a content of 87.6% and 12.4%, respectively. The electron paramagnetic resonance (EPR) spectra of these substances were also studied, and their distinctive features were identified. Additionally, the changes in the energy band gap of P25 upon the deposition of Co and CuI clusters were determined through optical scattering spectra. It was found that while the well in the scattering spectrum reflecting the gap in the energy spectrum of P25 changes insignificantly upon the deposition of cobalt (Co) clusters, upon the deposition of copper iodide (CuI) clusters, an additional well appears in the long-wavelength region, which leads to an increase in the sensitivity of the catalyst to visible light. The optical absorption spectra indicated a significant reduction in photoinduced charge recombination in the S-Scheme P25/CuI compared to conventional photocatalysts that are decorated with metal cocatalysts. The comparative efficiency of the considered photocatalysts was studied using a methylene blue solution.